Green innovation dynamics in SMEs: Unraveling the interplay of approach, expenditure, and performance - Lufeng Li; Ghansham Das; Raza Ali Tunio; Aamir Ali Gopang; Shehriyar Memon (Sustainable Futures)
Green innovation is a key driver of sustainable development, yet many Malaysian SMEs struggle to implement it due to resource constraints and inadequate support systems. This study aims to explore the relationship between R&D expenditure, green innovation approaches, and sustainable business performance, emphasizing the moderating role of the latter. Using micro-econometric models and data from the Malaysian Department of Statistics and FMMS, our findings reveal that SMEs adopting proactive green innovation strategies significantly increase R&D investment, leading to enhanced green innovation outcomes. Moreover, sustainable business performance moderates these relationships, particularly in low-performing contexts where SMEs may resort to rent-seeking behaviors. These insights have significant implications for businesses, policymakers, and stakeholders. Strengthening support mechanisms and leveraging sustainable finance initiatives can help SMEs overcome resource limitations and drive long-term environmental and economic benefits. This study contributes to the literature by highlighting actionable strategies to foster green innovation in SMEs.